ANALISIS PERFORMA BOILER BASUKI BERDASARKAN RASIO ANTARA BAHAN BAKAR DAN STEAM DI PT. INDO ACIDATAMA Tbk. - Maedanu Fasola Putra; Danar Susilo Wijayanto; Nugroho Agung Pambudi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The research aims to investigate the condition of Basuki boiler based on the ratio between fuel consumption and steam production. The research used quantitative-descriptive method. The population of this research was daily record of Basuki boiler. The sample was daily record of Basuki boiler performance for 1 year (February 2015 to January 2016). The sample was taken using purposive sampling method. The research analyzed the ability of fuel to produce a ton (1000 kilograms) of steam. The ability of fuel was depended on the highest heating value (HHV) and water contain in the coal. Based on the result of the research, it can be concluded that Basuki boiler condition based on its ratio between fuel consumption and steam production was good, because the ratio that shown (144.09) was less than the company’s target (150), it meant that the boiler only used 144.09 kilograms of coal to produce a ton of steam. The average of fuel consumption for 1 year was 1,484.99 kg/h and the average of steam production was 10,305.76 kg/h.